An Analysis Figurative Language Used in Jakarta Post Headline - Rima Novia Ulfa; Tiarma Ika Yuliana; Rr. Astri Indriana Octavita (STKIP PGRI Tulungagung, 2022)
The purpose of this research is going to analyse the types of figurative language in Jakarta Post Headline from November 2016 until January 2017 editions by using Keraf’s theory. This research uses qualitative approach with content analysis. In this study, the writer collected the data by selecting, reading and highlighting the figurative language in Jakarta Post Headline. The types of figurative language included in this research are metonym, eponym, metaphor, synecdoche, personification, and simile..